2020
DOI: 10.1096/fj.201902202r
|View full text |Cite
|
Sign up to set email alerts
|

A dual role for Tbx1 in cardiac lymphangiogenesis through genetic interaction with Vegfr3

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Thus, the distribution of Tbx1 -fated cells likely reflects a wave of activation that expands in different regions of the growing brain vascular network, rather than the deployment of Tbx1 -expressing EC progenitors and their progeny. The fact that the brain vascular phenotype was only detectable after E13.5, is consistent with the interpretation that critical TBX1 functions are in differentiated ECs and not in EC progenitors, in contrast, for example to the role of TBX1 in cardiac lymphatic vessels (Martucciello et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the distribution of Tbx1 -fated cells likely reflects a wave of activation that expands in different regions of the growing brain vascular network, rather than the deployment of Tbx1 -expressing EC progenitors and their progeny. The fact that the brain vascular phenotype was only detectable after E13.5, is consistent with the interpretation that critical TBX1 functions are in differentiated ECs and not in EC progenitors, in contrast, for example to the role of TBX1 in cardiac lymphatic vessels (Martucciello et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…We asked whether over-expression of Vegfr3 in the Tbx1 expression domain would rescue the brain vessel abnormalities of Tbx1 mutant embryos. To this end, we crossed Tbx1 Cre/+ mice with mice carrying a single copy of a Cre-activatable murine Vegfr3 transgene, TgVegfr3 mice (Martucciello et al, 2020). We then intercrossed mice with the genotypes Tbx1 Cre/+ ;TgVegfr3 and Tbx1 lacZ/+ and measured brain vessel density and filopodial density in E18.5 embryos with the following genotypes: Tbx1 +/+ , Tbx1 Cre/+ , Tbx1 Cre/lacZ , TgVegfr3; Tbx1 Cre/+ and TgVegfr3; Tbx1 Cre/lacZ that were immunostained with anti-GLUT1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although our recent data demonstrate that angiotensin II markedly increases VEGFR‐3 expression and lymphangiogenesis in mouse LECs though the angiotensin type I receptor, 30 the precise mechanisms by which pressure overload regulates VEGF‐C or VEGFR‐3 expression in LECs remain unclear. A previous study has shown that Tbx1, a member of the T‐box family of transcription factors, can upregulate VEGFR‐3 expression in endothelial cells by binding to an enhancer element within the Vegfr‐3 gene 31 . This prompted us to examine Tbx1 expression in TAC‐operated hearts.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that Tbx1, a member of the T-box family of transcription factors, can upregulate VEGFR-3 expression in endothelial cells by binding to an enhancer element within the Vegfr-3 gene. 31 This prompted us to examine Tbx1 expression in TACoperated hearts. We found that there were similar expression patterns between Tbx1 and VEGF-C or VEGFR-3 during the transition from adaptive cardiac hypertrophy to TAC-induced HF (supplementary material online, Figure S4C), suggesting that Tbx1 may be involved in regulating VEGF-C or VEGFR-3 expression in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The heart has an extensive lymphatic vessel network comprising a heterogeneous origin and signaling that regulates its development [ 230 , 231 , 232 , 233 , 234 , 235 ]. In a mouse MI model [ 236 ], cardiac lymphatic vessel impairment leads to interstitial fluid accumulation and myocardial fibrosis progression due to increased interstitial fluid pressure that might induce CF activation through mechanical stress within the ECM [ 237 ].…”
Section: Cardiac Lymphaticsmentioning
confidence: 99%